2007
DOI: 10.1002/ajmg.a.31678
|View full text |Cite
|
Sign up to set email alerts
|

A case of de novo partial tetrasomy of distal 6p and review of the literature

Abstract: We report on a 3-year-old girl with bilateral eyelid colobomas, bulbous nose, blepharophimosis, blepharoptosis, sensorineural hearing loss, atrial septal defect, psychomotor retardation, and growth delay. Cytogenetic analysis showed additional material of unknown origin on the short arm of chromosome 8. Whole chromosome paint FISH identified the additional material to originate from chromosome 6. Subtelomeric metaphase FISH analysis detected a bright signal pattern for the 6p subtelomere probe on the derivativ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
12
1

Year Published

2009
2009
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 9 publications
(11 reference statements)
0
12
1
Order By: Relevance
“…A single duplication overlapping this segment has been reported previously (14), but with no association with hearing impairment at 3 years of age. Duplications of this region have also been reported, mainly in association with ocular developmental anomalies and glaucoma (19); however, hearing impairment has not been noticed, except in a patient with a de novo partial tetrasomy of 6p25 (20). At least eight microdeletions within or overlapping this segment have been reported (15) associated with phenotypes much more severe than in our patient; phenotypes associated with deletions are frequently more severe than with duplications.…”
Section: Discussioncontrasting
confidence: 47%
“…A single duplication overlapping this segment has been reported previously (14), but with no association with hearing impairment at 3 years of age. Duplications of this region have also been reported, mainly in association with ocular developmental anomalies and glaucoma (19); however, hearing impairment has not been noticed, except in a patient with a de novo partial tetrasomy of 6p25 (20). At least eight microdeletions within or overlapping this segment have been reported (15) associated with phenotypes much more severe than in our patient; phenotypes associated with deletions are frequently more severe than with duplications.…”
Section: Discussioncontrasting
confidence: 47%
“…The HLA cluster genes on 6p and IRF4 (6p25.3) could play a crucial role in determining immune-system disorders, including the proliferative disorders Andrieux et al, 2006;Shaffer et al, 2009]. In addition, observing the previously reported phenotypes and karyotypes, in particular the cases of Scott et al [2007] and Stohler et al [2007], it could also be concluded that genes that are responsible for the partial 6p trisomy syndromes are those located between 6p25.1 and p25.2, and they could be: ECI2, NRN1,FARS2,TUBB2A,TUBB2B,SERPINB1,SERPINB6,SERPINB9,NQO2,RIPK1 ,and/or BPHL. It should be considered that all of the aforementioned genes can have analogues in the deleted regions that are associated with 6p trisomies ( table 2 ). Previously reported cases could be reinterpreted in the light of new discoveries in the field of cytogenetics and molecular biology.…”
Section: Discussionmentioning
confidence: 85%
“…Intellectual disability, epilepsy, mental retardation, autism, brain abnormalities, hearing loss, ocular defects, or immunodeficiency with susceptibility to pulmonar infections have also been reported [Smith and Pettersen, 1985;Fryns et al, 1986;Burd et al, 1988;Krassikoff and Sekhon, 1989;Katafuchi et al, 1992;Wauters et al, 1993;Giardino et al, 2002;Bart et al, 2011]. Furthermore, this chromosome anomaly is associated with a reduced life span [Villa et al, 2000;Stohler et al, 2007].…”
mentioning
confidence: 99%
“…20,22 The terminal 6p deletion of this patient includes a single Online Mendelian Inheritance in Man (OMIM) annotated gene, IRF4, which is not known to be dosage sensitive. The proximal duplication of interstitial 6p includes 51 OMIM annotated genes, including FOXC1, deletions and duplications of which have been associated with ocular abnormalities and DandyWalker malformation.…”
Section: Discussionmentioning
confidence: 99%
“…17,18 Genetic etiologies, including chromosomal and subtelomeric duplicated or deleted sequences, can be identified in ∼20% to 40% of cases. 17,19 Previously, both 6p 20 and 12q subtelomeric trisomies 21 were reported among genetic rearrangements associated with developmental delay.…”
mentioning
confidence: 99%